Li-ion battery aging test & data analytics - Sim, Xiao Hui (Nanyang Technological University, 2022)
With the rising popularity of Li-ion batteries, the ability to attain accurate estimation of the battery core and surface temperature is of crucial importance to ensure the operational performance, safety, and reliability usage of Li-ion batteries.